Kepemimpinan Gereja yang Efektif Di Era Society 5.0 - Parulian S, Panca; Sukamto, Amos; Pribadi, Liviana (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
Churches always exist in a particular context and always choose to respond to the development of culture or civilization, including Society 5.0. Society 5.0, based on technology, provides the concept of a human-centered society and the integration between the virtual world and the real world, which is often expressed by the term super-smart society. Is the church ready for this civilization? To answer that question, we need a big picture of the leadership that exists in the church. By using eight dimensions of culture and leadership from the Global Leadership and Organizational Behavior Effectiveness, this article seeks to create a picture of the leadership culture in the church based on the congregation's perspective, to be taken into consideration for leadership in the church in the Society 5.0 era. The researcher uses the basic survey method to describe church leadership. The results of the church's descriptive analysis tend to future orientation, performance orientation, assertiveness, human orientation, and collectivism. However, the church needs to pay special attention to the cultural dimension of uncertainty avoidance that tends to hinder the flexibility of church leaders.AbstrakGereja yang selalu hadir dalam konteks tertentu, selalu memiliki pilihan untuk merespons perkembangan budaya atau peradaban, termasuk Society 5.0. Society 5.0 dengan basis pemanfaatan teknologi memberikan konsep human-centered society dan integrasi antara dunia maya dan dunia nyata, yang sering diungkapkan dengan istilah super smart society. Apakah gereja siap dengan peradaban ini? Untuk menjawab pertanyaan  itu, diperlukan gambaran besar mengenai kepemimpinan yang ada di dalam gereja. Dengan menggunakan delapan dimensi budaya dan kepemimpinan dari Global Leadership and Organization Behaviour Effectivness artikel ini berupaya membuat gambaran budaya kepemimpinan yang ada di dalam gereja berdasarkan perspektif jemaat, untuk dijadikan bahan pertimbangan kepemimpinan dalam gereja di era Society 5.0. Peneliti menggunakan metode survei dasar dengan tujuan untuk menggambarkan kepemimpinan gereja. Hasil analisis deskriptif gereja memiliki kecenderungan pada future orientation, performance orientation, assertiveness, human orieentation, dan kolektivisme. Namun, gereja perlu memiliki perhatian khusus pada dimensi budaya uncertainty avoidance yang cenderung dapat menghambat fleksibilitas pemimpin gereja.